"A War of Ideas": The Rise of Conservative Teachers in Wartime New York City, 1938–1946. Issue 2 (May 2015) - Burkholder, Zoë
Abstract : On the evening of May 17, 1946, more than 1, 200 festive supporters streamed into the Brooklyn Academy of Music to honor a New York City teacher who had survived, by the skin of her teeth, charges of "un-American" teaching. Since 1935, New York City's public school teachers faced the threat of investigation and dismissal for potentially subversive radical political beliefs or affiliations. Tonight, however, the audience breathed a collective sigh of relief that the Board of Education hearing had turned out well and that the teacher in question would retain her position.